Perhelatan kenduri sko sebagai sebuah pesan kebudayaan masyarakat Kerinci di taman nasional Kerinci Seblat - Asvic Helida (Masyarakat, Kebudayaan dan Politik, 2016)
Kerinci society is indigenous tribe Indonesia inhabit Kerinci District, Jambi. They have various art and traditional ceremony that still exist until recent times. Kenduri sko is a form of customary prayer one that was held annually as an act of gratitude to God almighty for different harvest product. A message Kenduri sko an oral culture that has lasted hearts long time and hereditary. The cultural ceremony contains precious message such as integration, familiarity, awareness, togetherness and openness that become a fundamental factors to philosophy development to indigenous villagers in Kerinci. to reveal traditional ceremony Kenduri Sko of Kerinci as an oral tradition that has been occured for years and to deliver messages behind such tradition. The study was conducted in Dusun Baru Lempur Gunung Raya Sub District, Kerinci District in the month in October 2013 for 3 months. The approach used was conducted qualitatively by observation method through in-depth interviews with leaders of indigenous communities. there are cultural message that shows knowledge and natural resource utilization wisely and the realization to preserve natural resources.